Goal-ontology ETL processes specification - Ta'a, Azman; Abdullah, Mohd Syazwan; Md Norwawi, Norita (UUM Press, 2011)
The design-related problems for extract, transform, load (ETL) processes are far away from being resolved due to the ambiguity of user requirements and the complexity of operations.Current approaches are based on existing software requirement methods that have limitations on reconciliation of the requirement semantics toward generating the ETL processes specification.The solution is to apply the RAMEPs (Requirement Analysis Method for ETL Processes) that was developed to facilitate the design of the ETL processes in the perspectives of organization, decision-maker, and developer.The results are the ETL processes specification, which was validated on the correctness of the goal-ontology model and evaluated in the case study of Gas Malaysia Data Warehouse (DW) system.The case study illustrated how the goal-ontology approach was successfully implemented in designing and generating the ETL processes specification.